Integration of Dental Health into School Curriculum: A Comparison of Models from 5 Countries - Sutrisman, Henny; Padua, Shirley A; Sicat, Alvin S; Ramadhona, Rossa; Simanjuntak, Rosmerry; Kusumo, Bayu; Prihartanto, Adrianus (The Future of Education Journal, 2025)
Dental health among school-aged children is a critical issue that directly impacts quality of life and academic achievement. This article examines models for integrating dental health education into school curricula in Indonesia and other countries to formulate effective strategies for the national context. The methodology involves a literature review with an international comparative study approach. The analysis reveals that countries such as Finland, Japan, Malaysia, and New Zealand have successfully implemented relevant, effective, and sustainable intervention models. Drawing from these best practices, this article recommends developing a hybrid model for Indonesia that integrates daily thematic activities, collaboration with healthcare professionals, and active engagement of parents and communities within the education system.